Adsorption mechanism of recovering potassium from seawater by modified-clinoptilolite using microwave - Hao Guo (Journal of Water Reuse and Desalination, 2018)
The adsorption capacity and mechanism of K+ ion onto modified-clinoptilolite (MC) for recovering potassium from seawater has been investigated in this paper. The maximum value of K+ adsorption capacity is 36.3 mg/g (1.92 times of raw-clinoptilolite) while the modifying condition of microwave power is 450 W and heating time is 60 min. Specific surface area and pore size of absorbent has also been advanced with employing microwave. The kinetic data followed the pseudo-second-order model kinetic model, and the equilibrium data were well fitted to the Langmuir model, showing monolayer coverage of K+ ions on the surface pores of MC. Thermodynamic parameters, including Gibbs free energy (∆G), enthalpy changes (∆H), and entropy changes (∆S) were also calculated. The results demonstrated that K+ ion was absorbed onto MC spontaneously and exothermically in nature. Thus, MC could be employed as efficient and suitable adsorbent for recovering potassium from seawater.